Ethanol Induces Secretion of Proinflammatory Extracellular Vesicles That Inhibit Adult Hippocampal Neurogenesis Through G9a/GLP-Epigenetic Signaling - Zou, Jian; Walter, T. Jordan; Barnett, Alexandra; Rohlman, Aaron; Crews, Fulton T.; Coleman, Leon G. (Frontiers in Immunology, 2022)
Adult hippocampal neurogenesis (AHN) is involved in learning and memory as well as regulation of mood. Binge ethanol reduces AHN, though the mechanism is unknown. Microglia in the neurogenic niche are important regulators of AHN, and ethanol promotes proinflammatory microglia activation. We recently reported that extracellular vesicles (EVs) mediate ethanol-induced inflammatory signaling in microglia. Therefore, we investigated the role of EVs in ethanol-induced loss of adult hippocampal neurogenesis. At rest, microglia promoted neurogenesis through the secretion of pro-neurogenic extracellular vesicles (pn-EVs). Depletion of microglia using colony-stimulating factor 1 receptor (CSFR1) inhibition in vivo or using ex vivo organotypic brain slice cultures (OBSCs) caused a 30% and 56% loss of neurogenesis in the dentate, respectively, as measured by immunohistochemistry for doublecortin (DCX). Likewise, chemogenetic inhibition of microglia using a CD68.hM4di construct caused a 77% loss in OBSC, indicating a pro-neurogenic resting microglial phenotype. EVs from control OBSC were pro-neurogenic (pn-EVs), enhancing neurogenesis when transferred to other naive OBSC and restoring neurogenesis in microglia-depleted cultures. Ethanol inhibited neurogenesis and caused secretion of proinflammatory EVs (EtOH-EVs). EtOH-EVs reduced hippocampal neurogenesis in naïve OBSC by levels similar to ethanol. Neurogenesis involves complex regulation of chromatin structure that could involve EV signaling. Accordingly, EtOH-EVs were found to be enriched with mRNA for the euchromatin histone lysine methyltransferase (Ehm2t/G9a), an enzyme that reduces chromatin accessibility through histone-3 lysine-9 di-methylation (H3K9me2). EtOH-EVs induced G9a and H3K9me2 by 2-fold relative to pn-EVs in naïve OBSCs. Pharmacological inhibition of G9a with either BIX-01294 or UNC0642 prevented loss of neurogenesis caused by both EtOH and EtOH-EVs. Thus, this work finds that proinflammatory EtOH-EVs promote the loss of adult hippocampal neurogenesis through G9a-mediated epigenetic modification of chromatin structure.